‘I cannot be what I don’t see’: an evaluation of Academic Intersectionality Mentoring in medical schools (AIMMS Mentoring) - Mirembe Woodrow; Elizabeth Benedikz; Louise D Bryant; Jane Illés; Parbir Jagpal; Hannah Maria Jennings; Eleanor Monks; Vrinda Nayak; Musarrat Maisha Reza; Sikha Saha; Meena Upadhyaya; Kate Williams; et al. (PLoS ONE, 2025)
The Academic Intersectionality Mentoring in Medical Schools (AIMMS Mentoring) scheme aims to support the career progression of women from ethnic minority backgrounds working in academic medicine and health sciences who are under-represented in senior roles of academia in the UK. Two questionnaires (baseline and 6 months) captured information about AIMMS Mentoring participants and practical aspects of the scheme. Participants were asked about their experience of and satisfaction with the scheme, whether it matched their expectations and what they felt were the scheme’s rewards and challenges. Questions were also asked about the organisation of the scheme and how it could be improved. The productivity of mentoring relationships was explored, including personal and professional development, and whether participants felt it important that mentoring takes place between people with similar characteristics. Sixteen pairs took part in mentoring, with ten mentees and four mentors completing evaluation questionnaires at 6m follow-up. Responses indicated that the scheme was helpful. All mentor and mentee responses reported personal and professional development. Mentee responses in particular reported gaining insight into career development, and both groups felt they had gained understanding about institutional ways of working. Participants rated the scheme positively and indicated they would recommend it to others. Being in mentoring relationships with women from similar backgrounds was ascribed value, as was mentor partners being empathetic. The evaluation revealed ways in which the scheme could be improved. Women from ethnic minorities working in academic medicine and health sciences can face structural barriers into leadership. This formative and summative evaluation of AIMMS Mentoring showed that mentoring and peer support in this group is valuable and can assist with personal, professional and career development. The scheme is an example of positive action and a model national activity aimed at achieving equity of opportunity in academic medicine and health sciences.